Brief Report: Rituximab for the Treatment of Adult‐Onset IgA Vasculitis (Henoch‐Schönlein). Issue 1 (1st December 2017) - Maritati, Federica; Fenoglio, Roberta; Pillebout, Evangeline; Emmi, Giacomo; Urban, Maria L.; Rocco, Rossana; Nicastro, Maria; Incerti, Monia; Goldoni, Matteo; Trivioli, Giorgio; Silvestri, Elena; Mohammad, Aladdin J.; et al.
Abstract : Objective: Adult‐onset IgA vasculitis (Henoch‐Schönlein) (IgAV) is a rare systemic vasculitis characterized by IgA1‐dominant deposits. The treatment of adult‐onset IgAV is controversial and is based on the combination of glucocorticoids and immunosuppressive agents, but many patients have refractory or relapsing disease despite treatment. Rituximab (RTX) is a B cell–depleting antibody of proven efficacy in antineutrophil cytoplasmic antibody–associated vasculitis. We undertook this study to test the efficacy and safety of RTX in a multicenter cohort of patients with adult‐onset IgAV. Methods: In this multicenter observational study, we included patients with adult‐onset IgAV who had received RTX either for refractory/relapsing disease or because they had contraindications to conventional glucocorticoid/immunosuppressive therapy. We analyzed the rates of remission (defined on the basis of the Birmingham Vasculitis Activity Score [BVAS]) and relapse as well as the variations over time in estimated glomerular filtration rate (GFR), proteinuria, C‐reactive protein (CRP) level, BVAS, and prednisone dose. Results: Twenty‐two patients were included; their median duration of follow‐up was 24 months (interquartile range 18–48 months). Sixteen patients received RTX as add‐on therapy and 6 as monotherapy. Twenty patients (90.9%) achieved remission, and 7 of those 20 patients (35%) had subsequent relapse of disease. There were significant reductions in 24‐hour proteinuria ( P < 0.0001), CRP level ( P = 0.0005), BVAS ( P < 0.0001), and prednisone dose ( P < 0.0001) from RTX initiation through the last follow‐up visit; estimated GFR remained stable. RTX was generally well tolerated. One patient died after 60 months of follow‐up. Conclusion: Our data suggest that RTX is an effective and safe therapeutic option for adult‐onset IgAV.